2016
DOI: 10.1016/j.socscimed.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Numbers and narratives: Developing a mixed-methods approach to understand mobility in later life

Abstract: The aim of this methods-focused article is to explore the potential benefits of integrating GPS, diary and in-depth interview data to gain richer insights into the everyday mobility practices of older adults. Eighteen adults, aged 65-90 years, living in the Netherlands, participated in the study. Our findings illustrate how quantitative (GPS) and qualitative (interviews and diary-based) approaches together can generate different insights and layers of understanding from each individual method in order to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The present study examines the habitual travel behaviour of e-bike users by combining perceived and actual travel behaviour characteristics. In general, the value of combining these data has widely been recognized in the social sciences (Driscoll et al 2007) and mobility and transport studies (Meijering & Weitkamp 2016;Grosvenor 1998;Clifton & Handy 2003). We formulated three research questions: (1) What were motives for purchasing and starting to use an e-bike?…”
Section: Travel Behaviour In Research and Policymentioning
confidence: 99%
“…The present study examines the habitual travel behaviour of e-bike users by combining perceived and actual travel behaviour characteristics. In general, the value of combining these data has widely been recognized in the social sciences (Driscoll et al 2007) and mobility and transport studies (Meijering & Weitkamp 2016;Grosvenor 1998;Clifton & Handy 2003). We formulated three research questions: (1) What were motives for purchasing and starting to use an e-bike?…”
Section: Travel Behaviour In Research and Policymentioning
confidence: 99%
“…Only three studies quantitatively investigated the differences between weekday and weekend activity spaces (Kamruzzaman and Hine, 2012; Chen and Akar, 2016; Kang et al, 2017) with one finding that utilitarian walking was more likely to occur on weekdays than recreational walking (Kang et al, 2017). Two of the qualitative studies described how activity was patterned by day (Bell et al, 2015a; Meijering and Weitkamp, 2016) and found unique activities occurring at the weekends (Bell et al, 2015a) and differences in times and geographies of older adults' mobilities over different days depending on factors such as weather and availability of family (Meijering and Weitkamp, 2016).…”
Section: Methods Employedmentioning
confidence: 99%
“…Some studies addressed differences between potential access and actual usage by capturing broader spaces experienced over a day or week to identify a range of spaces that may be accessible to an individual, or by comparing features within an activity space with those accessible from a home address (Zenk et al, 2011; Chaix et al, 2016; Hirsch et al, 2016; Rundle et al, 2016). Ten studies used qualitative analysis to understand why particular environments were chosen for use (Vine et al, 2012; Bell et al, 2015b, 2015a; Milton et al, 2015; Loebach and Gilliland, 2016b; Meijering and Weitkamp, 2016; Franke et al, 2017; Plazier et al, 2017; Yoo and Kim, 2017; Hand et al, 2018).…”
Section: Methods Employedmentioning
confidence: 99%
“…Although gerontology has often organized its theories around activity and wellbeing, space or spatial behavior remain neglected in its early theoretical articulations. This neglect is more intensified in the context of developing countries (notable exceptions include [4][5][6]). For instance, the last few decades in social gerontology have been dominated by the Successful Aging paradigm that defines 'success' within the narrow parameters of low disease probability or disease-related disability, high levels of physical and cognitive functioning, and active engagement in life.…”
Section: Introductionmentioning
confidence: 99%